Beyond the energy balance: Exergy analysis of an industrial roller kiln firing porcelain tiles. (5th March 2019) - Ferrer, S.; Mezquita, A.; Aguilella, V.M.; Monfort, E.
Highlights: The energy and exergy efficiency of a ceramic tile roller kiln was evaluated. The main factors affecting thermal efficiency in firing ceramic tiles are described. The single-deck roller kiln exhibited low energy performance, namely about 15%. More than 60% of the energy input into the kiln was lost through the exhaust gas stacks. The exergy destroyed by irreversibilities accounted for 83% of the total exergy input into the kiln. Abstract: The ceramic tile manufacturing process consumes large amounts of energy, mainly in the firing stage. Firing usually takes place in natural gas-fuelled continuous roller kilns, the most widely used tile firing facilities worldwide, which typically exhibit low energy efficiency (generally 5 to 20%). This paper investigates the application of energy and exergy balances to an industrial roller kiln firing porcelain tiles in order to identify the most critical parameters affecting kiln energy efficiency and propose ways of improving kiln energy performance. The experimental kiln measurements and thermodynamic calculations confirmed the kiln's low energy performance (15%). Exergy analysis showed that 83% of the total exergy input into the kiln was destroyed, only 10% of the exergy input being kept in the physico-chemical transformations of the ceramic tile composition. The main sources of irreversibilities: natural gas combustion, heat transfer in the fired tile cooling process, and heat transfer through the kiln surfaces, were identified and quantified. The study shows that waste heat (over 61%) recovery could be expected to significantly increase kiln energy performance. Finally, further measures are proposed for optimising kiln energy efficiency.